The Effects of Short Delay Times on Rock Fragmentation - Margaret Hettinger; Dr. Catherine Johnson; Joseph Nawrocki (International Society of Explosives Engineers, 2016)
"Optimized rock fragmentation is essential for minimizing downstream costs to mining operations.Photographic fragmentation analysis, vibration monitoring, and high-speed video all providemeasurements of blast effectiveness and supply data that allows operations to modify blasts to achieve downstream goals."